Uničujoči vpliv medijskega nasilja na družbene predstave in zaznave - Kraner, David (Bogoslovni vestnik, 2025)
Negative media content has a destructive impact on our perception of others and on social representations. Negative affects, images, and messages often aim to distance individuals from critical evaluation and analytical debate. In contrast, media content can be constructive, especially when it consists of positive images, examples, and encouraging practices with which audiences can identify. Such representations are rare, as they are often displaced by negative or destructive ones. These are reinforced by negative and aggressive messages presented as “entertainment,” as well as by exploitation, deception, and media propaganda. Theories of media effects confirm the claim that a greater presence of constructive content would contribute to increased peace among individuals and within society, while at the same time resulting in less profit for the media and their affiliated agencies.
Keywords: dobiček; entertainment; media effects; media violence; medijski učinki; medijsko nasilje; profit; social representations; socialne reprezentacije; zabava